Optimal. Leaf size=24 \[ 3-e^{\frac {e^{e^x} \left (-2+\frac {2}{x^2}\right ) x}{\log (2)}} \]
________________________________________________________________________________________
Rubi [F] time = 5.03, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {e^{e^x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}} \left (2+2 x^2+e^x \left (-2 x+2 x^3\right )\right )}{x^2 \log (2)} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\frac {\int \frac {e^{e^x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}} \left (2+2 x^2+e^x \left (-2 x+2 x^3\right )\right )}{x^2} \, dx}{\log (2)}\\ &=\frac {\int \frac {2 e^{e^x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}} \left (1-e^x x+x^2+e^x x^3\right )}{x^2} \, dx}{\log (2)}\\ &=\frac {2 \int \frac {e^{e^x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}} \left (1-e^x x+x^2+e^x x^3\right )}{x^2} \, dx}{\log (2)}\\ &=\frac {2 \int \left (\frac {e^{e^x+x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}} \left (-1+x^2\right )}{x}+\frac {e^{e^x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}} \left (1+x^2\right )}{x^2}\right ) \, dx}{\log (2)}\\ &=\frac {2 \int \frac {e^{e^x+x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}} \left (-1+x^2\right )}{x} \, dx}{\log (2)}+\frac {2 \int \frac {e^{e^x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}} \left (1+x^2\right )}{x^2} \, dx}{\log (2)}\\ &=\frac {2 \int \left (e^{e^x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}}+\frac {e^{e^x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}}}{x^2}\right ) \, dx}{\log (2)}+\frac {2 \int \left (-\frac {e^{e^x+x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}}}{x}+e^{e^x+x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}} x\right ) \, dx}{\log (2)}\\ &=\frac {2 \int e^{e^x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}} \, dx}{\log (2)}+\frac {2 \int \frac {e^{e^x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}}}{x^2} \, dx}{\log (2)}-\frac {2 \int \frac {e^{e^x+x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}}}{x} \, dx}{\log (2)}+\frac {2 \int e^{e^x+x+\frac {e^{e^x} \left (2-2 x^2\right )}{x \log (2)}} x \, dx}{\log (2)}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.95, size = 23, normalized size = 0.96 \begin {gather*} -e^{-\frac {2 e^{e^x} \left (-1+x^2\right )}{x \log (2)}} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.69, size = 33, normalized size = 1.38 \begin {gather*} -e^{\left (\frac {x e^{x} \log \relax (2) - 2 \, {\left (x^{2} - 1\right )} e^{\left (e^{x}\right )}}{x \log \relax (2)} - e^{x}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} \int \frac {2 \, {\left (x^{2} + {\left (x^{3} - x\right )} e^{x} + 1\right )} e^{\left (-\frac {2 \, {\left (x^{2} - 1\right )} e^{\left (e^{x}\right )}}{x \log \relax (2)} + e^{x}\right )}}{x^{2} \log \relax (2)}\,{d x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.07, size = 22, normalized size = 0.92
method | result | size |
risch | \(-{\mathrm e}^{-\frac {2 \left (x -1\right ) \left (x +1\right ) {\mathrm e}^{{\mathrm e}^{x}}}{x \ln \relax (2)}}\) | \(22\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.56, size = 26, normalized size = 1.08 \begin {gather*} -e^{\left (-\frac {2 \, x e^{\left (e^{x}\right )}}{\log \relax (2)} + \frac {2 \, e^{\left (e^{x}\right )}}{x \log \relax (2)}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 5.90, size = 25, normalized size = 1.04 \begin {gather*} -{\mathrm {e}}^{\frac {2\,{\mathrm {e}}^{{\mathrm {e}}^x}-2\,x^2\,{\mathrm {e}}^{{\mathrm {e}}^x}}{x\,\ln \relax (2)}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.45, size = 19, normalized size = 0.79 \begin {gather*} - e^{\frac {\left (2 - 2 x^{2}\right ) e^{e^{x}}}{x \log {\relax (2 )}}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________